Herbal Mineral Block Supplementation Containing Turmeric Flour, Black Soldier Fly, and Micro Minerals on Performance and Blood Profile of Dorper Crossbred Sheep - Daulay, Kausar; Astuti, Dewi Apri; Suharti, Sri; Tarigan, Andi (Buletin Peternakan, 2024)
This study aimed to determine the effect of herbal mineral block (HMB) supplementation containing turmeric flour, black soldier fly (BSF), and micro minerals on the performance and blood profile of Dorper crossbred sheep. Ten growing sheep and ten lactating sheep were divided into two treatment groups (P0: complete feed without HMB supplementation and P1: complete feed with HMB supplementation). The research design used was a factorial completely randomized design (2 × 2) with 5 replications. Factor physiological status of growing and lactating sheep and factor supplementation with and without HMB. The data were analyzed using ANOVA and Duncan’s test. The results showed no interaction between physiological status and HMB supplementation on sheep performance (nutrient intake, initial and final body weight, daily body weight gain, and feed efficiency) and blood profile (hematology, metabolites, and minerals). The physiological status had a very significant effect (p<0.01) on nutrient intake, initial and final body weight, daily body weight gain, feed efficiency, and significantly (p<0.05) on serum phosphorus. Supplementation of HMB significantly (p<0.05) increased serum calcium which was crucial for bone an teeth development in growing sheep and milk production in lactating sheep. Serum phosphorus was higher in growing sheep, supporting their bone growth and energy metabolis compared to lactating sheep as it was diverted to the mammary gland.